The Uniqueness of Waqf Land Disputes Resolution Denied by Some Heirs (Case Study of Waqf in Pondok Pesantren X Jombang Jawa Timur) - Hikmah, Nur Yaumil; Hartini; Robiyantoko, Joesoef Shidqi Marsa; Al Firdaus, Irfan Aziz (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This paper discusses a handover of land for waqf from Mrs. Setyowati (a pseudonym) to Pondok Pesantren X (a pseudonym) around 1993-1998 in Jombang, East Java which is done not in front of a Waqf Pledge Deed Official or Pejabat Pembuat Akta Ikrar Wakaf (PPAIW). The waqf done by wakif had not been registered as waqf land at Office of Religious Affairs or Kantor Urusan Agama (KUA), a substitution deed is required, because the wakif has passed away. During the certification process, some heirs chose to deny the waqf done by their mother due to economic factor and the waqf around 1993—1998 contain a legal flaw. The nazhir chose nyusuki to the heirs as a form of dispute resolution because it is considered a win-win solution. This research is empirical juridical research. This research shows that the act of nyusuki by the nazhir is an effective form of waqf dispute resolution in an amicable manner due to the denial of the waqf by some heirs of the wakif. Although it violates the waqf rules in Indonesia, there are benefits that arise from the act of nyusuki, namely contributing to the smooth development of new educational unit of Pondok Pesantren X so that waqf purpose can be achieved.